Surgical treatment of squamous cell cancer with anal margin localization developed on the background of condyloma acuminata: A case report - Lale, Azmi; Yur, Mesut; Aygen, Erhan (My University, 2020)
We present the treatment of squamous cell carcinoma (SCC) with anal margin localization on the basis of condyloma acuminata bylocal excision. A 65-year-old male patient had complaints of bleeding, constipation and itching in the anal area. Physical examinationrevealed a 5x4 cm ulceration and an irregular mass in the anal margin localization. The incisional biopsy exposed a SCC thatdeveloped on the background of condyloma acuminata. Tumor was resected with ulcerated condyloma akumita and the skin defectwas successfully repaired with V-Y plasty. In conclusion well differentiated superficial invasive anal carcinomas (T1N0) can besuccessfully treated by local excision.
Keywords: Genel ve Dahili Tıp; Cerrahi